Dysbiosis of Gut Microbiota Is Associated With the Progression of Radiation-Induced Intestinal Injury and Is Alleviated by Oral Compound Probiotics in Mouse Model - Zhao, Tian-Shu; Xie, Li-Wei; Cai, Shang; Xu, Jia-Yu; Zhou, Hao; Tang, Lin-Feng; Yang, Chao; Fang, Shuguang; Li, Ming; Tian, Ye (Frontiers in Cellular and Infection Microbiology, 2021)
The acute radiation-induced intestinal injury (RIII) has raised much concerns and is influenced by non-cytocidal radiation effects including the perturbations in gut microbiota. Although a number of studies have reported alteration in gut microbiota following radiation, little is known about its dynamic variation in the progression of acute RIII. In this study, mouse model were treated with total body irradiation (TBI) of 0, 4, 8 and 12 Gy, and the intestinal tissues and fecal samples were collected at 6 h, 3.5 d and 7 d post radiation. We found that the intestinal injuries were manifested in a radiation dose-dependent manner. Results from 16S rRNA gene sequencing demonstrated that the diversity of gut microbiota was not significantly affected at the prodromal stage of acute RIII, after 6 h of radiation. At the critical stage of acute RIII, after 3.5 d of radiation, the composition of gut microbiota was correlated with the radiation dose. The Pearson’s correlation analysis showed that the relative abundances of phylum Proteobacteria, genera Escherichia-Shigella and Eubacterium xylanophilum_group, and species Lactobacillus murinus exhibited linear correlations with radiation dose. At the recovery stage of acute RIII, after 7 d of radiation, the diversity of gut microbiota decreased as a whole, among which the relative abundance of phyla Proteobacteria and Bacteroides increased, while that of phylum Tenericutes and genus Roseburia decreased. The intra-gastric administration of compound probiotics for 14 days improved the survival duration of mice exposed to 9 Gy TBI, alleviated the intestinal epithelial injury and partially restored the diversity of gut microbiota. Our findings suggest that acute RIII is accompanied by the dysbiosis of gut microbiota, including its decreased diversity, reduced abundance of beneficial bacteria and increased abundance of pathogens. The gut microbiota cannot be used as sensitive biomarkers at the prodromal stage in acute RIII, but are potential biomarkers at the critical stage of acute RIII. The dysbiosis is persistent until the recovery stage of acute RIII, and interventions are needed to restore it. The administration of probiotics is an effective strategy to protect against acute RIII and subsequent dysbiosis.